DAIVAVYAPASRAYA (MANTRA) CHIKITSA IN AYURVEDA - Chumi Bhatta1*; Khagen Basumatary; Loukrakpam Victoria Devi; Victoria Boro (AYUSHDHARA, 2018)
Ayurveda is not merely a science of therapeutics based on herbal, animal and mineral resources of medicament but deals with philosophy of life and living being. For treatment Charak classified the treatment principle in, 1.Daivavyapasraya chikitsa, 2. Yuktivyapasraya chikitsa, 3. Sattavajaya chikitsa. In Daivavyapasraya chikitsa, Daiva comes in relation to karma which is done in Purvajanma. Daivavyapasraya is the spiritual therapy related to blessings and influence of god and consist of Mantra, Ausadhi, Mani dharan, Mangal, Bali, Upahar, Homa, Niyama, Prayachitta, Upavasa, Swastaayana, Pranipata and Yatragamana. Here the mantras are the sacred words having spiritual potency. It means a sound, combination or sequence of sound develop spontaniously. Their power is not in the word themselves but in the sound vibration created when they are uttered verbally. Mantra – the sound therapy of healing effect on the body, mind and spirit through the movement of tongue, the mouth and it changes the chemical in brain which relaxes the brain wave, detoxify the mind, cleansing the cellular toxin. Mantra instil confidence, improve concentration and sound therapy in the medicine of the future, sound as a carrier wave of consciousness protects us from several diseases and reforms the future.